Implementasi dan Dampak Audit Internal Syariah di BNI Syariah Branch Office Surabaya. - Hediana, Demara; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2019)
Islamic financial institutions are currently growing rapidly. Based on the data from the Financial Services Authority in 2018 there were 34 Islamic Banking in Indonesia. From this data, 13 include Sharia Commercial Banks (BUS) and the other 21 are the Sharia Business Units (UUS). As the growth of Islamic financial institutions, it requires internal control in carrying out banking operations. Therefore, this study aims to determine the implementation and impact of the internal sharia audits at BNI Syariah Branch Office Surabaya. This study uses a qualitative descriptive method and in-depth interview. The results of this study indicate that the implementation impact of sharia internal audits are in accordance with the applicable standard. Particularly the impact of sharia internal audits increases the effectiveness and efficiency of banking activities both in terms of accounting control and administrative control.